Construction of a Sinorhizobium meliloti strain carrying a stable and non-transmissible chromosomal single copy of the green fluorescent protein GFP-P64L/S65T - Pistorio, Mariano (2002)
A single copy of the green fluorescent protein (GFP)-encoding gene gfp-P64L/S65T under the control of the constitutive nptII promoter was introduced in a neutral region of the Sinorhizobium meliloti chromosome, between the genes recA and alaS. Within the same chromosomal region downstream of gfp-P64L/S65T a tetracycline (Tc) resistant cassette was also inserted. Both markers were very stable during at least 40 bacterial generations without any selective pressure. Similarly, the gfp-Tc cassette was stable and functional in all rhizobia that were recovered from alfalfa nodules. The GFP-associated fluorescence derived from the (single copy) chromosomal gfp-P64L/S65T allowed detection of rhizobia during the colonisation of the root, infection thread formation, and nodule development. The gfp-Tc rhizobia showed indistinguishable phenotypes for nodulation, competitiveness, and nitrogen-fixation from the parental strain. The labelling system described here can be used for the stable fluorescent tagging of S. meliloti strains allowing their detection in biologically complex soil environments.